A case of catatonia in the aftermath of the COVID-19 pandemic: does autism spectrum matter? - Liliana Dell’Osso; Giulia Amatori; Camilla Gesi; Claudia Carmassi (Annals of General Psychiatry, 2021)
Abstract Background There is growing concern about the psychopathological consequences of the COVID-19 pandemic. The prolonged stress due to the spreading fear of the contagion and to the enforced containment measures are deemed to trigger recurrences of preexisting mental disorders as well as the onset of new ones. From such perspective, clinical cases may be of primary ground to identify individual features and pandemic-related factors predisposing to the development of serious psychiatric symptoms. Case presentation Mr. R. is a 64-year-old, married, unemployed man, whose premorbid personality was characterized by relevant autistic traits. The patient developed catatonia in the context of the COVID-19 pandemic. We aimed at discussing the role of both preexisting and precipitating factors. Conclusions Autism spectrum could represent a predisposing factor for severe psychopathological outcome and catatonia. Furthermore, the present clinical case highlights the role of COVID-19 pandemic in influencing physical and mental health.